Activating Consumers for Better Service Coproduction outcomes through Eustress: The Interplay of Firm-Assigned Workload, Service Literacy, and Organizational Support. (April 2017) - Mende, Martin; Scott, Maura L.; Bitner, Mary Jo; Ostrom, Amy L.
Companies are allocating increasing coproduction workloads to consumers. Ironically, many consumers may be ill-equipped to coproduce, as indicated by widespread low service literacy (e.g., financial literacy, medical literacy). This research examines how consumers, particularly those low in service literacy, respond to varying levels of firm-assigned coproduction workload. Five studies, including a hospital field experiment, reveal three findings. First, service literacy plays a moderating role, such that higher (vs. lower) levels of coproduction workload improve service outcomes (e.g., compliance intentions), particularly for consumers with low service literacy. Second, coproduction eustress is a crucial mediator, such that positive service outcomes result from consumers appraising coproduction tasks as positive and meaningful challenges. In turn, eustress is elicited by consumers' belief that they are collaborating with the provider to achieve a shared goal. Third, offering organizational support to consumers might mitigate the beneficial effects of coproduction eustress because it can trigger reactance. This research can help policy makers and managers in finding new ways to activate consumers, particularly those low in service literacy, as coproducers for better service outcomes.